Specific Inhibition of Acyl-CoA Oxidase-1 by an Acetylenic Acid Improves Hepatic Lipid and Reactive Oxygen Species (ROS) Metabolism in Rats Fed a High Fat Diet - Zeng, Jia (J Biol Chem, 2017)
A chronic high fat diet results in hepatic mitochondrial dysfunction and induction of peroxisomal fatty acid oxidation (FAO); whether specific inhibition of peroxisomal FAO benefits mitochondrial FAO and reactive oxygen species (ROS) metabolism remains unclear. In this study a specific inhibitor for the rate-limiting enzyme involved in peroxisomal FAO, acyl-CoA oxidase-1 (ACOX1) was developed and used for the investigation of peroxisomal FAO inhibition upon mitochondrial FAO and ROS metabolism. Specific inhibition of ACOX1 by 10,12-tricosadiynoic acid increased hepatic mitochondrial FAO via activation of the SIRT1-AMPK (adenosine 5′-monophosphate-activated protein kinase) pathway and proliferator activator receptor α and reduced hydrogen peroxide accumulation in high fat diet-fed rats, which significantly decreased hepatic lipid and ROS contents, reduced body weight gain, and decreased serum triglyceride and insulin levels. Inhibition of ACOX1 is a novel and effective approach for the treatment of high fat diet- or obesity-induced metabolic diseases by improving mitochondrial lipid and ROS metabolism.